Long‐term oncological and reproductive outcomes of fertility‐sparing cytoreductive surgery in females aged 25 years and younger with malignant ovarian germ cell tumors. Issue 3 (10th December 2013) - Ertas, Ibrahim Egemen; Taskin, Salih; Goklu, Rifat; Bilgin, Muzaffer; Goc, Goksu; Yildirim, Yusuf; Ortac, Firat
Abstract Aim To evaluate the long‐term oncological and reproductive outcomes of patients aged 25 years and younger who were treated by fertility‐sparing cytoreductive surgery (FSCS) plus adjuvant chemotherapy (ACT) or observation alone for malignant ovarian germ cell tumors (MOGCT). Methods Records of 42 eligible female patients treated for MOGCT between 1 May 1995 and 31 December 2010 at two centers were analyzed retrospectively. A telephone questionnaire was performed to gather reproductive and menstrual history. Results One patient was treated without FSCS and two patients were lost to follow‐up. The mean age of the remaining 39 patients was 18.4 ± 3.2 years. Eighteen of the tumors were histologically pure dysgerminomas (PD) and 21 were non‐dysgerminomatous tumors (non‐DT). Thirteen patients (33%) presented with stage II–III disease. Optimal cytoreduction was achieved in 34 of the 39 patients (87%). Systematic pelvic and para‐aortic lymphadenectomy was performed in 31 of the 39 patients (79.5%). The frequency of lymph node metastasis was 29% (9/31). Twenty‐seven patients (69.2%) received ACT. Disease recurred in six (15.3%) patients, all in the non‐DT group. Four of six underwent secondary optimal FSCS followed by chemotherapy. Retroperitoneal nodal recurrence was detected in two of these four patients (50%). Four deaths occurred, three due to chemoresistant aggressive disease and one due to secondary acute myelocytic leukemia. The overall survival rates for patients with PD and non‐DT were 100% and 81.4%, respectively. Twenty‐three of 27 patients who received ACT continued their regular menses. Sixteen spontaneous pregnancies and one pregnancy by intrauterine insemination were achieved by 21 patients who attempted conception. Conclusion Either primary or secondary FSCS followed by ACT seems to be a feasible and safe approach to preserving future fertility and hormonal function in young patients with MOGCT.